El conjunto histórico del Recinto de Golfito: principios para una gestión integrada - Riba-Hernández, Lucía (2012)
The headquarters of the University of Costa Rica at Golfito were built during the Banana Enclave Period in the South Pacific Region of the country. Among all the buildings, specifically two, the Old Headquarters and the Central Club have been declared as Historic Architectural Heritage. A Synthesis of the background and principles that have guided the investigations and intervention process, as determinants to face the new academic needs and the responsibility of safeguarding part of the national Cultural Heritage, is depicted.